2008
DOI: 10.1039/b806271d
|View full text |Cite
|
Sign up to set email alerts
|

Inner reorganization during the radical–biradical transition in a nor-β-lapachone derivative possessing two redox centers

Abstract: In this work, the electrochemical behaviour of an antitumoral nitro o-quinone derivative obtained from 3-bromo-nor-beta-lapachone was studied. Cyclic voltammetric experiments, in acetonitrile solution, revealed that both quinone and nitro functions are reduced independently as quasi-reversible one-electron transfer processes in this order. Depending on the reduction potential, a radical anion or a biradical dianion is obtained. The formation of these paramagnetic species was confirmed by performing in situ Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This behavior is consistent with the presented mechanism of reduction of this compound. Both radical species behave independently in the same structure, as already described for the reduction of independent redox centers that also generate stable biradical dianionic species [47]. This independent behavior of both radical species indicates that inductive effects which allow the transport of electrons from the reduced sites do not allow a proper coupling of the electron spins being added upon reduction of the respective sites in the molecule (at -NO 2 groups at positions C-3 and C-5 and the COOCH 3 function at C-1), which would not be the case if resonant effects were present (as in ortho or para substituted compounds).…”
Section: Electrochemistry and Esr-spectroelectrochemistry Of Methyl 3mentioning
confidence: 68%
“…This behavior is consistent with the presented mechanism of reduction of this compound. Both radical species behave independently in the same structure, as already described for the reduction of independent redox centers that also generate stable biradical dianionic species [47]. This independent behavior of both radical species indicates that inductive effects which allow the transport of electrons from the reduced sites do not allow a proper coupling of the electron spins being added upon reduction of the respective sites in the molecule (at -NO 2 groups at positions C-3 and C-5 and the COOCH 3 function at C-1), which would not be the case if resonant effects were present (as in ortho or para substituted compounds).…”
Section: Electrochemistry and Esr-spectroelectrochemistry Of Methyl 3mentioning
confidence: 68%
“…According to the previous paper for the reduction of the same compound in acetonitrile, on glassy carbon electrode, 13 the second cathodic peak appearing at a more negative potential would correspond to the further one-electron reduction of the electrogenerated radical anion in order to obtain a quinone-nitro biradical dianion, according to Equation 5:…”
Section: Resultsmentioning
confidence: 99%
“…13 Therein, it was shown that both quinone and nitro functions are reduced independently as quasi-reversible one-electron transfer processes and afford different radical ion species. Depending on the reduction potential, the presence of a radical anion or a biradical dianion was confirmed by performing in-situ Electrochemical-Electron Spin Resonance (E-ESR) experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…electron spin resonance, ESR), would give important structural information. 14 In protic medium, electrochemical studies on DNA and also in the presence of biologically important thiols like N-acetylcysteine (NAC) can be performed 15 to test the Michael acceptor nature of this quinone, 10,11 which would favour its pro-oxidant nature, with relevance in antitumor activity. 12,16,17 More specifically, the use of NAC is relevant once it has been used as tools for investigating the role of ROS (reactive oxygen species) in numerous biological and pathological processes.…”
Section: Introductionmentioning
confidence: 99%